2003
DOI: 10.1002/adsc.200303014
|View full text |Cite
|
Sign up to set email alerts
|

Baeyer–Villiger Monooxygenases, an Emerging Family of Flavin‐Dependent Biocatalysts

Abstract: Abstract:Baeyer±Villiger monooxygenases (BVMOs) are flavoenzymes that catalyze a remarkably wide variety of oxidative reactions such as regioand enantioselective Baeyer±Villiger oxidations and sulfoxidations. Several of these conversions are difficult to achieve using chemical approaches. Due to their selectivity and catalytic efficiency, BVMOs are highly valuable biocatalysts for the synthesis of a broad range of fine chemicals. For a long time, only one member of this class of flavin-containing biocatalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
159
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(168 citation statements)
references
References 123 publications
6
159
0
3
Order By: Relevance
“…These proteins are extensively studied for their exploitation in biocatalytic applications (2,3). This interest follows the problems related to the toxicity and instability of the oxidizing reactants that are currently being used in chemical processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are extensively studied for their exploitation in biocatalytic applications (2,3). This interest follows the problems related to the toxicity and instability of the oxidizing reactants that are currently being used in chemical processes.…”
mentioning
confidence: 99%
“…We have expressed and purified several monooxygenases (2,8), and the only protein that so far produced crystals suited for x-ray analysis is phenylacetone monooxygenase (PAMO) from the moderate thermophilic bacterium Thermobifida fusca. PAMO is a monomeric 62-kDa enzyme that catalyses the conversion of phenylacetone to phenylacetate ( Fig.…”
mentioning
confidence: 99%
“…However, this cascade is currently limited to NADPH due to the strict cofactor recognition of the CHMO from Acinetobacter sp. NCIMB 9871 (CHMO Acineto ), [4] a well-known BaeyerVilliger monooxygenase (BVMO) for lactone synthesis. From an industrial perspective, NADH is the preferred cofactor as it is cheaper (up to 30 times) and more stable than NADPH.…”
mentioning
confidence: 99%
“…[6] The majority of BVMOs including CHMO Acineto belongs to the NADPH-dependent type I BVMOs. [4] Up to date, there are several studies devoted to change the cofactor specificity of BVMOs through protein engineering. [7] One recent study on switching the cofactor specificity of CHMO Acineto has been reported by the group of Bornscheuer.…”
mentioning
confidence: 99%
“…However, the conversion of 9 into 11 by G. candidium CCT 1205 in aqueous phosphate (pH 6.5) did not even reach 3% within 48 h. On the other, the lower pH was found essential to activate the BVMO of T. cutaneum CCT 1903, as almost 30% of the starting 9 was converted into 11 within 48 h. In both cases the intermediate 10 was never detected, probably due to the action of hydrolytic enzymes such as lipases or esterases, as previously mentioned. 14 As reviewed recently, BVMOs are classified according to substrate specificity, 18 therefore BVMOs of G. candidum CCT 1205 and T. cutaneum CCT 1903 belong to different groups. Therefore, probe-substrates for enzyme activity must be carefully selected as "you get what you screen for".…”
Section: Screening For Bvmomentioning
confidence: 99%